Key audit matters and investors’ reactions / Nor ‘Asyiqin Abu ...[et al.] - Abu, Nor ‘Asyiqin; Jaffar, Romlah; Rahmat, Mohd Mohid; Hassan, Mohamat Sabri (UiTM Press, 2021)
The new requirement of International Standards on Auditing (ISA) 701 specifies that auditors must highlight key audit matters (KAMs) found in the financial statements audit of listed companies commencing in December 2016. As proposed by standard setters, KAMs are considered crucial to be highlighted to shareholders due to the clarity that KAMs provide regarding audited financial statements. However, findings from various countries indicate that there are mixed investors’ reactions to KAMs. Therefore, this study examined the relationship between KAM disclosure and investors’ reactions among 931 firm-year observations on Malaysian Public Listed Companies from 2016 to 2019. The number of KAMs, new matters in KAMs, and recurring KAMs were the independent variables, whereas the share price served as a dependent variable to represent investors’ reactions. The results of ordinary least squares (OLS) and fixed effect regression indicated that KAMs do not affect share prices, even when they interact with going concern opinions. Additionally, the findings indicated that investors’ reactions were mostly prompted by a company’s financial performance and governing characteristics rather than by KAMs. The findings contribute to the literature on KAMs and investors’ reactions, especially in the Malaysian context.